The suppressive effect of REVERBs on ghrelin and GOAT transcription in gastric ghrelin-producing cells. (December 2021) - Iijima, Mio; Takemi, Shota; Aizawa, Sayaka; Sakai, Takafumi; Sakata, Ichiro
Abstract: Ghrelin is a multifunctional gut peptide with a unique structure, which is modified by a medium chain fatty acid at the third serine by ghrelin O -acyl transferase (GOAT). It is well known that the major source of plasma ghrelin is the stomach, but the transcriptional regulation of gastric ghrelin and GOAT is incompletely understood. Here, we studied the involvement of the nuclear receptors REV-ERBα and REV-ERBβ on ghrelin and GOAT gene expression in vivo and in vitro . Reverse-transcriptase polymerase chain reaction analysis showed that REV-ERBα and REV-ERBβ mRNAs were expressed in the stomach and a stomach-derived ghrelin cell line (SG-1 cells). In vivo experiments with mice revealed the circadian rhythm of ghrelin, GOAT, and REV-ERBs. The peak expression of ghrelin and GOAT mRNAs occurred at Zeitgeber time (ZT) 4, whereas that of REV-ERBα and REV-ERBβ was observed at ZT8 and ZT12, respectively. Treatment of SG-1 cells with SR9009, a REV-ERB agonist, led to a significant reduction in ghrelin and GOAT mRNA levels. Overexpression of REV-ERBα and REV-ERBβ decreased ghrelin and GOAT mRNA levels in SG-1 cells. In contrast, small-interfering RNA (siRNA)-mediated double-knockdown of REV-ERBα and REV-ERBβ in SG-1 cells led to the upregulation in the expression of ghrelin and GOAT mRNAs. These results suggest that REV-ERBs suppress ghrelin and GOAT mRNA expression.